Sonographic And Histopathological Study Of Mammary Tumours In Female Dogs (Applied Biological Research, 2022)
The study was conducted on mammary tumour in ten female dogs which  were presented to the Veterinary Clinical Complex of the university. The female dogs were of different breeds with age ranging between 5.0 and 16.5  years (median age 10.7). The ultrasonographic images were used to evaluate the shape, size and echogenicity of mammary lesions. In ign tumours were homogenous in their internal  echogenic pattern i.e. hypoechoic. Ultrasonograms of malignant tumour  ike structure of variable sizes having hyperechoic  boundary. Excisional biopsy was taken after the surgery of these cases. Of  the clinical 10 cases, 6 were of benign whereas the rest cases were of  malignant category. Due to the request of owners of the animals, surgeries  were performed and tumours were confirmed by histopathology. There  were four cases of adenocarcinoma, two cases each of benign mixed tumours and myoepithelioma and one case each of adenoma and myxoma.  Skin sutures were removed after 12 days. Post-operativecarwas done  antibiotics (ceftriaxone + tazobactum), analgesics (meloxicam), B complex and vitamin C injections for 5 days. The study suggested that  ultrasonography alone is sufficient to diagnosebenign and malignant
Keywords: Dog; histopathology; malignant; mammary tumour; ultrasonography